Observation of Charmonium Sequential Suppression in Heavy-Ion Collisions at the Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review Letters, 2026)
We report measurements of charmonium sequential suppression in Ru+Ru and Zr+Zr collisions at sNN=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The inclusive yield ratio of ψ(2S) to J/ψ as a function of transverse momentum is reported, along with the centrality dependence of the double ratio, defined as the ψ(2S) to J/ψ ratio in heavy-ion collisions relative to that in p+p collisions. In the 0-80% centrality class, the double ratio is found to be 0.41±0.10 (stat)±0.03 (syst)±0.02 (ref), lower than unity with a significance of 5.6 standard deviations. This provides experimental evidence that ψ(2S) is significantly more suppressed than J/ψ in heavy-ion collisions at RHIC. This sequential suppression pattern seems to increase from peripheral to central collisions, but with no significant dependence on the transverse momentum. © 2026 American Physical Society.
Keywords: dept.phy